The students’ participation and achievement in English on different seating arrangements - Handayani, Qanita; Amrullah, Amrullah; Apgrianto, Kurniawan (Yayasan Mitra Persada Nusantara, 2023)
Seating arrangements play a crucial role in education, but traditional approaches may not meet students' needs. This research is a comparative experimental approach using the concurrent embedded mixed-method research approach to investigate whether different seating arrangements (separate tables and horseshoe) shows a sinificant difference on students' participation potentials and achievement in English. This study explores students’ participation and achievement potential in different seating arrangements (separate tables and horseshoe) on 8th-grade students' participation and achievement in English. Data from 50 students at SMPN13 Mtm were collected through observations, quetionnaire surveys, and tests, analyzed using qualitative and quantitative methods. The findings revealed significant differences in participation potentials across certain indicators, with separate tables enhancing motoric and mental activities and horseshoe arrangements benefiting visual and writing activities. However, both arrangements showed no significant difference in listening, oral, and emotional activities. In terms of achievement, the study revealed significant differences in students' achievement on different seating arrangements students with separate tables achieved higher academic performance compared to the horseshoe arrangement. These results indicate that seating arrangements influence students' participation and achievement, suggesting alternative seating options for implementation in classrooms, with consideration of specific factors.